Prevalence and Risk Factors for Unruptured Intracranial Aneurysms in the Population at High Risk for Aneurysm in the Rural Areas of Tianjin - Liu, Jie; Zou, Xuan; Zhao, Yan; Jin, Zhangning; Tu, Jun; Ning, Xianjia; Li, Jidong; Yang, Xinyu; Wang, Jinghua (Frontiers in Neurology, 2022)
Although the prevalence of unruptured intracranial aneurysm (UIA) lies between 2% and 5%, the consequences of aneurysm rupture are fatal. The burden of UIA is considerable in stroke patients. However, the best prevention and management strategy for UIA is uncertain among patients with a family history of stroke. Therefore, this study aimed to determine the epidemiological characteristics and risk factors for UIA based on a population with a family history of stroke. This study used random sampling to recruit participants with a family history of stroke among rural residents in Jixian, Tianjin, China. All participants underwent a questionnaire survey, physical examination, and cervical computed tomography angiography (CTA). CTA data were used to determine whether the subjects had UIA. The relationship between relevant factors and UIA was assessed using logistic regression analysis. A total of 281 residents were recruited in this study, with a mean age of 50.9 years. The prevalence of UIA in those with a family history of stroke was 10.3% overall (9.8% among men and 10.9% among women). Moreover, with each unit increase in body mass index (BMI), the prevalence of UIA decreased by 12.5%. Particularly among non-obese men, BMI had a stronger protective effect (OR: 0.672; 95%CI: 0.499–0.906; P=0.009), and among non-obese men, an increase in low-density lipoprotein (LDL) was associated with an increased prevalence of UIA (OR: 3.638; 95%CI: 1.108–11.947; P=0.033). Among the non-obese with a family history of stroke, BMI may be protective against UIA, especially in men. It is crucial to strictly control the LDL level in non-obese people to reduce the burden of UIA.